A technical and tactical profile of the double olympic judo champion: A case study - Adam, M.; Smaruj, M.; Laskowski, R. (International Journal of Sports Science and Coaching, 2014)
The technical and tactical analyses of judo competitions are frequently discussed in the literature, yet individual profiling is scarce. The aim of the study was to determine the technical and tactical profile of one of the world's best judokas in the history of judo. Waldemar Legien' is a retired Polish judoka and winner of two Olympic gold medals in different weight classes (78 kg and 86 kg). The present research on his career spans the period of 1991 to 1992, during which he competed in 24 tournaments, both at home country and abroad. His outstanding winning record could potentially lie in the fact that he employed techniques from each group of throws. His repertoire of nineteen different techniques, including throws and grapplings, attests to his technical excellence. Our study suggests that one distinctive feature of Legien' as a super elite judoka was his technical and tactical versatility.